Analisis Kinerja Protokol AODV (Ad Hoc On-Demand Distance Vector) dan AOMDV (Ad Hoc On-Demand Multipath Distance Vector) Terhadap Serangan Aktif Pada Jaringan Manet (Mobile Ad Hoc Network) - Muhammad Alif Bahari; Primantara Hari Trisnawan; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
MANET (Mobile Ad hoc Network) is a network that does not have a fixed infrastructure and the nodes in it function as routers to forward the information that is sent. MANET has 3 types of routing protocols, namely proactive, reactive and hybrid routing protocols. AODV (Ad Hoc On Demand Distance Vector) and AOMDV (Ad Hoc On Demand Multipath Distance Vector) are reactive type protocols found on MANET. Security on MANET is a big challenge, because nodes will be connected to one unprotected wireless network. Based on the above problems, the authors made a study entitled Performance Analysis of AODV Protocol and AOMDV Against Active Attacks on MANET (Mobile Ad hoc Network) networks. The results obtained from this study are proven that active attacks in the form of Blackhole and DDoS attacks of type Flooding RREQ Attack affect the performance of the two protocols. Tests in this study were conducted on Network Simulator 2 and measured based on 3 parameters, namely Packet Delivery Ratio, End-To-End Delay, and Normalized Routing Load. The test results show that the lowest value of Packet Delivery Ratio is found in the 100 node scenario using the AOMDV protocol with the type of DDoS attack that is worth 52.00%. While the highest end-to-end delay value is found in the 100 node scenario using the AODV protocol with DDoS attack types that are worth 134.25 ms. The highest average value of Normalized Routing Load is found in the 100 node scenario using the AOMDV protocol with DDoS attack types valued at 158.8.